Transformasi Bidang Litbang Menjadi Badan Riset dan Inovasi Daerah Provinsi Bali - I Made Agus Gelgel Wirasuta (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
Bung Karno/Sukarno (the first president of Indonesia) placed research as the main ingredient in planning the Pola Pembangunan Semesta Berencana and used the research results on an ongoing basis to realize the ideals of national development, namely: "Welfare with social justice for all Indonesian people (Kesejahteraan yang berkeadilan sosial bagi seluruh masyarakat Indonesia)", and increase the nation's competitiveness. The Law No. 11 of 2019 concerning the National System of Science and Technology requires the role of local governments in the development of research, inventions, and innovations, as well as utilizing the results in the form of Intellectual Property. The transformation of the Regional Research and Development Institute is a must to carry out the mandate of the Law No. 11 of 2019. This study conveys the transformation of Bali's Regional R&D Agency (Litbangda) towards badan Riset dan Inovasi Daerah Provinsi (Regional Research and Innovation Agency of Bali Province).